Design of single-shot longitudinal bunch profile monitor based on analysis of coherent smith-purcell radiation - Harrison, H (2018)
The spectral analysis of coherent Smith-Purcell radiation (cSPr) is a promising new longitudinal diagnostic technique. This thesis presents a conceptual design for a single-shot, non-destructive, coherent Smith-Purcell radiation monitor and investigates the challenges of realising this type of diagnostic. It is proposed to use the polarization of coherent Smith Purcell radiation in order to distinguish it from background radiation. A series of experimental studies are carried out at the 8MeV electron accelerator LUCX (KEK, Japan) in order to measure the polarization of cSPr. An experimental setup is developed for measuring the frequency and polarization of low intensity THz frequency signals in accelerator environments. The frequency measurements are made with a Fabry-Perot interferometer, using wire grid polarizers as beamsplitters. The operation of this interferometer is shown to be comparable to classic interferometer designs. The results show cSPr to be highly polarized and easily distinguishable from unpolarized background radiation. Suggestions are made to improve the experimental setup in order to obtain more detailed measurements in the future. An investigation into the number and distribution of detection channels required in the cSPr monitor is also carried out. This demonstrates that significant savings in space and cost can be made by optimising the design for specific accelerator environments.